In Vitro Antimicrobial Susceptibility of Common Bacterial Keratitis Pathogens to Topical Ophthalmic Fluoroquinolones - Arabella R. Mendoza; Eleonore B. Iguban (Philippine Journal of Ophthalmology)
Objective: This study determined the in vitro susceptibility of three bacterial isolates, Pseudomonas aeruginosa, Staphylococcus aureus, and Streptococcus pneumoniae, to 11 commercially available topical ophthalmic fluoroquinolones: levofloxacin (Oftaquix and Leeflox), ofloxacin (Ofbeat and Inoflox), moxifloxacin (Vigamox and Vistamox), besifloxacin (Besivance), ciprofloxacin (Ciloxan and Celsus), and gatifloxacin (Zymar and Agatiflox).